Modifikasi Waktu Aging dan Konsentrasi Kitosan pada Enkapsulasi Mikrokapsul Silika-Chlorhexidine 2% untuk Aplikasi Drug Delivery Root Canal Treatment - Denny Nurdin; Enggar Dwi Kusuma; Bambang Sunendar Purwasasmita (Center for Material and Technical Product, 2014)
The rising complexity and needs of healthcare nowadays is demanding the science and engineering to bring out the new concept of health treatment that enabled more effective drug administration. Silica, known as one of the most potential resources in Indonesia even in the whole world, can cope with poor temperature and chemical stability limitations. Silica has a good compatibility and stability which can lead it to be a promising material to encapsulate bioactive or drug and effectively deliver them to human body. The used of sodium silicate as precursorwass intended to encapsulate the active substance, in this case was chlorhexidine 2%. The encapsulation was done by Stober process. By Stober process it is possible to produce spherical and monodispersed nanoparticles with controlable particle size and drug release rate in ambient temperature. This study was purposed to generate approximately 1 µm sized microcapsules of silica containing chlorhexidine digluconate 2% encapsulated with alginate and chitosan. Microcapsules were intended to be used in medicament root canal treatment. The Stober process was modified with aging time and consentration of chitosan solution to control the size of microcapsules. Varied aging times are 72 hours, 36 hours, 24 hours, 8 hours, and 4 hours. The most suitable modified result, which was 4 hours aging time with 100-500 nm particle size then soaked in chlorhexidine 2% and combined with alginate and chitosan in ratio 6% :2% to form clustered encapsulated microcapsule under 1 µm in size. The characteristics of microcapsules were observed by scanning electron microscopy, FTIR spectroscopy. The release rate of encapsulated active substance observed was forty minutes longer than the non-encapsulated, by UV-Visible spectroscopy. Perkembangan kehidupan manusia telah menuntut ilmu pengetahuan dan teknologi untuk menemukan cara terbaru bagi perawatan kesehatan dan teknik penyaluran obat. Silika sebagai sumber daya mineral terbesar di Indonesia bahkan di dunia berpotensi sebagai material yg dapat menyalurkan zat aktif ke dalam tubuh tanpa batasan efektivitas karena pengaruh suhu ataupun kestabilan kimia bahan itu sendiri. Pada penelitian ini dilakukan enkapsulasi zat aktif chlorhexidine 2% melalui proses Stober agar partikel yang dihasilkan berbentuk spherical dengan ukuran yang dapat dikontrol dan terdispersi secara merata. Sodium silikat digunakan sebagai precursor. Mikrokapsul yang dihasilkan ditujukan untuk perawatan saluran akar gigi. Proses Stober dilakukan dengan variansi waktu aging dan konsentrasi kitosan sebagai dispersan untuk mengontrol ukuran partikel. Waktu aging bervariasi mulai 72 jam, 36 jam, 24 jam, 8 jam, dan 4 jam. Dari variasi waktu aging, mikrokapsul terbaik akan dilakukan impregnasi chlorhexidine 2% dan dienkapsulasi dengan 6% kitosan 2% dan 2% alginat 0,5% sehingga didapatkan mikrokapsul dengan ukuran kurang dari 1 µm. Pada hasil sintesis kemudian dilakukan karakterisasi SEM, dan FTIR. Melalui UV-Vis diketahui waktu aktifdari zat aktif bertambah 40 menit dengan enkapsulasi.